Design of an IOT Based Autonomous Vehicle with the Aid of Computer Vision - Kanagarla Akhil, A.Lokesha Viswajith,Vathana D (International Journal of Advanced Science and Technology, 2020)
Right now web controlled and halfway independent vehicle framework is exhibited. The idea is to create a remotely operated car that could be powered over a confirmed database from anywhere using the Web. This vehicle has mechanization highlights like impediment shirking framework so it can drive itself securely. If there should be an occurrence of availability disappointment, the vehicle control is finished by the transmitter area with the assistance of web cam (Image preparing) and zigbee. The aim is to reduce the threat of human life and ensure the most prominent protection when driving.